2021
DOI: 10.1002/chem.202101182
|View full text |Cite
|
Sign up to set email alerts
|

Novel WS2/Fe0.95S1.05 Hierarchical Nanosphere as a Highly Efficient Electrocatalyst for Hydrogen Evolution Reaction

Abstract: Fe 0.95 S 1.05 with high reactivity and stability was incorporated into WS 2 nanosheets via a one-step solvothermal method for the first time. The resulted hybrid catalyst has much higher catalytic activity than WS 2 and Fe 0.95 S 1.05 alone, and the optimal WS 2 /Fe 0.95 S 1.05 hybrid catalyst was found by adjusting the feed ratio. The addition of Fe 0.95 S 1.05 was proven to be able to enhance the hydrogen evolution reaction (HER) activity of WS 2 , and vice versa. At the same time, it was found that the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…WS 2 possesses captivating characteristics, including high electrical conductivity, outstanding catalytic activity, and high thermochemical stability. Different morphologies of WS 2 have been extensively described and examined. Single and multilayer WS 2 can be achieved through sonication, hydrothermal, or chemical vapor deposition methods. Single and multilayer WS 2 exhibit outstanding catalytic activity toward H 2 production. WS 2 NPs, nanoflakes, and nanoflowers have been explored. Various synthesis techniques, including the hydrothermal, sono chemical method, solvothermal method, ultrasonic spray pyrolysis, colloidal method, chemical vapor deposition, and electrochemical method, have been reported for the synthesis of WS 2 . WS 2 appears as tremendously important NSs with peculiar characteristics like biocompatibility, large surface area, efficient photocatalyst, , excellent electrochemical activity, auspicious electronic properties, and high mobility …”
Section: Synthesis Biomedical Environmental and Energy Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…WS 2 possesses captivating characteristics, including high electrical conductivity, outstanding catalytic activity, and high thermochemical stability. Different morphologies of WS 2 have been extensively described and examined. Single and multilayer WS 2 can be achieved through sonication, hydrothermal, or chemical vapor deposition methods. Single and multilayer WS 2 exhibit outstanding catalytic activity toward H 2 production. WS 2 NPs, nanoflakes, and nanoflowers have been explored. Various synthesis techniques, including the hydrothermal, sono chemical method, solvothermal method, ultrasonic spray pyrolysis, colloidal method, chemical vapor deposition, and electrochemical method, have been reported for the synthesis of WS 2 . WS 2 appears as tremendously important NSs with peculiar characteristics like biocompatibility, large surface area, efficient photocatalyst, , excellent electrochemical activity, auspicious electronic properties, and high mobility …”
Section: Synthesis Biomedical Environmental and Energy Applicationsmentioning
confidence: 99%
“…327−330 WS 2 NPs, nanoflakes, and nanoflowers have been explored. 331−335 Various synthesis techniques, including the hydrothermal, 336 sono chemical method, 337 solvothermal method, 338 ultrasonic spray pyrolysis, 339 colloidal method, 340 chemical vapor deposition, 341 and electrochemical method, 342 have been reported for the synthesis of WS 2 . WS 2 appears as tremendously important NSs with peculiar characteristics like biocompatibility, 343 large surface area, efficient photocatalyst, 344,345 excellent electrochemical activity, 346 auspicious electronic properties, and high mobility.…”
Section: Cobalt Sulfidementioning
confidence: 99%
“…In the S 2p XPS spectra (Figure 3b), two peaks located at binding energies of 162.5–162.7 and 163.6–163.9 eV can be assigned to the S 2p 3/2 and S 2p 1/2 of S 2− in WS 2 . [ 38 ] In the P 2p region (Figure 3c), two peaks at lower binding energies of 130.7–130.9 and 129.8–130.0 eV are assigned to P 2p 1/2 and P 2p 3/2 of P δ− in WP, respectively, confirming the formation of WP species. However, the other peak at a higher binding energy of 134.7–135.1 eV is attributed to PO x species due to surface oxidation in the air atmosphere, which is often observed in metal phosphides.…”
Section: Resultsmentioning
confidence: 75%
“…The W 4f XPS spectra (Figure 3a) can be deconvoluted into three doublets at binding energies of 32.8-33.0/ 34.9-35.1 eV (4f 7/2 /4f 5/2 ), 34.2-34.4/32.0-32.2 eV (4f 7/2 /4f 5/2 ), and 36.5-36.7/38.6-38.8 eV (4f 7/2 /5p 3/2 ), being ascribed to the W-P bonds, W 4þ in WS 2 , and WO x species due to the inevitable surface oxidation, respectively. [34,38] Interestingly, it is observed that the intensity of XPS peaks related to W-P bonds in CeP 5 O 14 / WP/WS 2 /CC is appreciably stronger than that in WP/WS 2 /CC. And the content of WP species in CeP 5 O 14 /WP/WS 2 /CC calculated by the deconvoluted W 4f XPS spectrum is 21.5 at%, much higher than that in WP/WS 2 /CC (6.5 at%).…”
Section: Surface Chemical States Of the Cep 5 O 14 /Wp/ws 2 /Cc Terna...mentioning
confidence: 99%
“…As is shown in Figure 3c, the Tafel slope of Ni 91 Ru 9 @NC-600(mix) is 42 mV • dec À 1 , which is much lower than those of Ni 91 Ru 9 @NC-400(fcc) (81 mV • dec À 1 ) and Ni 91 Ru 9 @NC-700(fcc) (66 mV • dec À 1 ). A low Tafel slope of a catalyst indicates that the HER rate could increases rapidly as the applied voltage increases, [30,31] which suggest better catalytic performance of Ni 95 Ru 5 @NC-600(mix) at higher current densities. To further elucidate the outstanding activity of the catalysts, electrochemical impedance spectroscopy (EIS) measurement was performed and the corresponding equivalent circuit was shown in the inset.…”
Section: Electrocatalytic Performance For Niru@nc Catalystsmentioning
confidence: 99%